Antenatal care quality measurement conducted by midwives in Karawang, Indonesia - Astri Nurdiana; Ella Nurlailasari (Journal of Health Technology Assessment in Midwifery, 2020)
Antenatal care standards currently deals with the implementation of 10T (Indonesian Abbreviation), which consist of measurements weight and height, blood pressure checks, examination of uterine fundus, Tetanus Toxoid immunization, administration of Fe tablets, assessment of nutritional status, laboratory tests, assessment of fetal heart rate and presentation, case management and counseling. This study aims to identify the implementation of antenatal care performed by midwives in Karawang District based on the 10 T antenatal care standards. This is a quantitative study, which used the descriptive-analytic design and was conducted for six months. The results showed that measurement of fundus height, nutritional status, TT immunization, determination of fetal heart rate as well as waiting time, reached a standard of above 85%. The measurements weight and height, administration of Fe tablets, tests laboratory, case management, counseling, and service duration are standard care with an achievement rate of less than 85%. The quality of midwifery service and compliance in conducting antenatal care according to the 10T standard need to be improved for early detection of complications to prevent maternal deaths in Karawang Regency.